OPTIMALISASI TEKNOLOGI MEDIA SOSIAL DAN BAHASA INGGRIS DALAM KEWIRAUSAHAAN DI ERA DIGITAL - Pastima Simanjuntak; Nurma Dhona Handayani; Daris Purba; Cosmas Eko Suharyanto (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
media or people are more familiar with calling it the term internet. This media is also referred to as a media that until now no one has matched the growth in the number of users. In developed countries, online media beats various media that have previously been used as a reference source in obtaining information. In the past few years, new media has been enlivened by the phenomenon of the emergence of social networking sites, these sites provide a place in the virtual world to build a community of friendship networks that can be accessed by everyone around the world. Social media is also a tool that has been available as a means to increase sales targets and can also be a means to find out the reach of all promotional activities carried out. With this technology strategy, it will bring change to society and can encourage various change efforts, because people still do not know about social media and English, many people, especially school children and teenagers who still do not understand the application of information technology and are still do not understand the application of English, therefore the purpose of this coaching is to invite the public to know about social media strategies and strategies for using English in the creative industry.